Firm heterogeneity, productivity, and the extensive margins of trade - differences between manufacturing firms in East and West Germany - Astrid Krenz (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
I investigate the relationship between the extensive margins of imports and exports (the number of countries traded with and the number of goods traded) and firm productivity using a newly constructed and rich panel data set of German manufacturing firms for the years 2009-2014. I do for the first time construct a data set based on German trade data and firm data that accounts for the substantial change in the German register of firms statistics after 2012. The extensive margins are significantly and positively associated with firm-level productivity both for West and East German firms in cross-sectional estimations, which is in line with the previous literature. Productivity is higher in firms that import and export more goods and trade with more countries. However, results based on panel analyses reveal that especially for East German firms the relationship becomes insignificant when unobserved firm heterogeneity is controlled for. The results point to a high degree of firm heterogeneity, of factors that are relevant and differ within the firm only, for firms in East Germany.
Keywords: F14; L25; L60; 330; Extensive margins of trade; Firm Productivity; Germany; Firm Heterogeneity